Crime, Justice, and Defoe : Law Enforcement Reported and Imagined in Eighteenth-Century England - Clegg, Jeanne, (Costerus New Series ;, 2025)
Having filched a little white bundle from under the noses of an apothecary's apprentice and his maid in London's Leadenhall Street, Defoe's Moll Flanders is sure that she will be "taken next time and be carry'd to Newgate and be Try'd for my Life". The likelihood of being arrested, tried and executed runs like an electric current through Moll's accounts of the many successful getaways that follow, and of how she negotiates her way out of the hands of her victims and would-be prosecutors, constables, magistrates and judges. These narratives cannot be understood in terms of the framework of law enforcement practice taken for granted by modern consumers of crime fiction and news reports. Crime, Justice, and Defoe brings to the surface assumptions embedded in both Moll Flanders and Colonel Jack about who might do or say what at a crime scene, before a J.P., in court, and during negotiations for a pardon, assumptions to which we are now culturally blind. For help with this, the book draws on social histories of crime and justice, on early modern prescriptive manuals, on magistrates' examinations of accused persons, and on reports of trials for property crime held at the Old Bailey in the early 1720s. It pays special attention to the changes taking place in law enforcement in Defoe's lifetime and asks how his fictions may have helped naturalise those changes, or hindered them. In the process, the book explores the multi-layered narrative techniques used to tell readers both what 'really' happened and how matters might - or should - have turned out differently.